The contribution of content analysis studies in the area of Special Education and its interface with prematurity - Luciana Pizzani; Juliana de Fátima Lopes; Mariana Gurian Manzini; Claudia Maria Simões Martinez (Universidade Federal de Santa Maria (UFSM), 2014)
To present the methodological procedures used to define categories of studies in the area of interface between prematurity and Special Education, supported by the methodology of Bardin's content analysis. The analysis' corpus were summaries of thesis and dissertations available in Thesis Database of Capes, involving the issue of prematurity in the period from 1987 to 2009. The sample included 1173 records, in which it is possible to distinguish two categories of targets: Main Theme (TP), studies whose subjects are connected directly to individuals premature; Thematic Secondary (TS): studies on the theme of prematurity appears as fruit or result of research conducted. A content analysis helped to identify the most studied aspects in the area of prematurity in Brazil, from the Capes Thesis Database, allowing to realize that this theme has been crafted in different areas of knowledge and multidisciplinary teams in an attempt to prevent or minimize disabling sequelae through stimulation and early intervention, since preterm birth can be considered a public health problem due to their high occurrence in the world.